Perancangan Penukar Panas (HE) Berbahan Bakar Sekam Padi Pada Pengering Ikan Dengan Kapasitas 50 KG - Aditiya Prastiya; Oleh Oleh; Aa Santosa (Peneliti.net, 2022)
Fish drying machine with a capacity of 50 kg of wet fish is one of the energy machines that serves to reduce the water content in fish by passing hot air of 40-50oC above its surface. This fish drying machine has a heat exchanger as its main heart. The source of heat energy used is the combustion of husks and air. Then with the heat exchanger the gas is flowed through the tube in the heat exchanger. The heat exchanger used is a cross flow type heat exchanger in which the air fluid mixes and the husk combustion gases do not mix. On the outside of the tube, drying air flows which will be heated and used as a drying medium for wet fish. The large heat flow rate carried by the drying air can reduce the water content in the grain by 31.2 kg of water from 50 kg of fresh fish in 8 hours. The heat exchanger construction planning is made in such a way using the LMTD approach and the effectiveness and CFD simulation integrated in Anys15.0, so that the performance of the tool can be known. The final result of modeling provides flow and temperature distribution that occurs in the heat exchanger. The capital uses 3D steady flow by selecting standard K-e as turbulence modeling and activating the energy equation. The input data entered into the application is the result of previous measurements and calculations.